Meningkatkan Aktivitas Dan Hasil Belajar Peserta Didik Menggunakan Model Prima Pada Kelas V Di Sekolah Dasar Negeri Tanjung Pagar 3 - Muhammad Oviananda Syauqi; Wahdah Refia Rafianti (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The purpose of this research is to describe the activities of educators and students and to analyze learning outcomes in the content of Citizenship Education. Efforts to increase activity and learning outcomes are through the Problem Based Learning, Think Pair Share, and Make A Match models or abbreviated as the PRIMA model. This study used Classroom Action Research (CAR). The subjects of this research were fifth grade students at Tanjung Pagar 3 Elementary School, totaling 35 students consisting of 24 male students and 11 female students. The results of this study indicate that the activity of educators at meeting 1 obtained a value of 57.50% with the criteria "Good enough", increased at meeting 4 to obtain a value of 100% with the criteria "Very Good". Student activity at meeting 1 reached 48.57% with the "Less Active" criteria increased at meeting 4 to 100% with the "Very Active" criteria. The completeness of the cognitive aspects of students' learning outcomes at meeting 1 obtained 62.85% classical completeness and at meeting 4 reached 100%. At meeting 1 classical completeness on the affective aspect 57.14% and psychomotor aspects 62.85%, increased at meeting 4 on the affective aspect obtaining 100% and psychomotor aspects obtaining 94.25%.